Enhancing moringa nutritive value for impoverished populations and healthy wellbeing through proper nutrient enrichment - Rufai, Shamsuddeen; Musa, Mohamed Hanafi; Yusop, Mohd Rafii; Mohidin, Hasmah; Kankara, S. S.; Hussaini, M. A.; Syed Rastan, Syed Omar (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Taking into account the many cases of malnutrition related deaths in especially sub-Saharan Africa, the current research effort was conceived with the objective of appraising the nutritive potential of Moringa oleifera L. plant through the evaluation of proper agronomic practice that will enhance its nutritive potential. Measured quantity of dried roots, stem, and leaves portions of 5 months old Moringa oleifera L. seedlings, grown under various applied phosphorus (P) and potassium (K) rates were analysed for essential and non-essential amino acids content, total antioxidants, secondary metabolites (phenolics and flavonoids), and mineral nutrient elements. The high-performance liquid chromatography (HPLC) analysis revealed the presence of 9 essential and 7 non-essential amino acids, with a range of 4.24 to 10.04 gkg-1 recorded for leucine, threonine, histidine, glutamic acid, aspartic acid, and glycine. The 2,2ꞌ- diphenyl-1-picrylhydrazyl (DPPH) and the ferric reducing antioxidant power (FRAP) assay revealed strong antioxidants presence (up to 68% DPPH scavenging activity and a high level FRAP potential of 2500 mg ascorbic acid equivalent (AAE) / 100g dry weight (DW). Folin-Ciocalteu’s and aluminium chloride calorimetric assay revealed high levels of secondary metabolites (ranging from 1000 to 1350 mg gallic acid equivalent (GAE)/100g DW total phenolics and up to 2400 mg quercetin equivalent (QE)/1mg DW total flavonoids), and the nitric acid wet digestion procedure revealed a lot of mineral nutrient elements (with significant values of up to 19.13 g kg-1 maximum content acquired from calcium (Ca) and up to 9.90 g kg-1 recorded for iron (Fe). These nutritive components are noted to be highest in the leaves portion, followed by the roots, and then the stem parts. Based on its recognised rich base nutritive content, Moringa oleifera L. is a tree plant of nutraceuticals importance for impoverished communities.